Prevalence and Related Factor of Asthma Towards Children Aged 13rd-14th in Rural Area - Wanami Putri, Ni Made Wini Jayesthiwi; Mayangsari, Ayu Setyorini Mestika; Sidiartha, I Gusti Lanang; Adnyana, I Gusti Agung Ngurah Sugitha (E-Jurnal Medika Udayana; Vol 11 No 3 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i03.P08, 2022)
There are 300 million people in all aged have an asthma, or it reach 1-16% prevalent of asthma in children worldwide. The study of prevalence and risk related factors of asthma in rural daerah is still very limited nowadays. The design of this study is cross-sectional quantitative study, with epidemiology analytic design. This study was conducted in Junior High School 1 in Sukawati, Sukawati Village, Gianyar, Bali. There are 557 samples of children aged 13 rd -14 th . The samples were collected based on constitutional sampling method. This study used ISAAC (International Study of Asthma and Allergies in Childhood) electronic questionnaires. The aims of this study was to determine the relation between prevalence of asthma and its related factors dermatitis atopic, allergies rhinitis, states of nutrition, atopic diseases in family, passive smokers, and fast food consumption in rural daerah in Bali. Prevalence of asthma in Bali in this study is 7.5%. Based on the analysis, allergic rhinitis (RP= 2.09 IK95%= 1.1-3.72 p= 0.01), atopic dermatitis (RP=4.33 IK95%=2.34-8.02 p=0.0001), and atopic diseases in family (RP= 2.56 IK95%=1.42-4.63 p=0.001), had a significant difference result with the prevalence of asthma. Besides, obesity (RP=0.98 IK95%=0.48-2.0 p=0.96), passive smokers (RP=1.52 IK95%=0.84-2.74 p=0.16), and fast food consumption (RP=1.24 IK95%=0.65-2.35 p=0.51), did not have any significant different result with the prevalence of asthma. Internal risk factors have a significant result towards the prevalence of asthma. Meanwhile, external risk factors need more exploration and research to know its effect on exacerbation and incident of asthma. Keyword: Asthma, ISAAC, Prevalence, Related Factors